Seismic Soft Soil-Structure Interaction Using RLBRB-Equipped Strut in Deep Excavations. Issue 7 (19th May 2022) - Khademalrasoul, Abdolghafour; Shirmohammadi, Arash; Pakbaz, Mohammad Siroos; Labibzadeh, Mojtaba
ABSTRACT: This paper presents the applicability of Reduced Length Buckling-Restrained Braces (RLBRBs) in combination with strut elements in deep excavations. Strut members are used as part of the lateral load resisting system. By proposing a new type of RLBRB section, the advantages of RLBRBs are demonstrated in dynamic soft soil-structure interactions. A numerical investigation is carried out to clarify the behavior of RLBRB-equipped strut members in supported deep diaphragm walls in soft clayey soils. The validity of the numerical models is confirmed after comparing the results of the nonlinear dynamic analyses with those of the experimental evidences. Four different excavations with 8 m, 12 m, 16 m and 20 m of clear bay spans and an excavation depth of 14 m are numerically simulated. In order to investigate the seismic analysis under various circumstances, three different accelerograms with various frequency contents are utilized. In the current study, the damping mechanism and the axial load bearing capacity of the RLBRBs in seismic conditions are taken into account in order to dissipate the induced earthquake energy and consequently preserve the local and global stability of the supported deep excavation. In this regard, one- and two-sided RLBRB-equipped struts with pipe-shaped steel cores are applied in a lateral stiffening system. As a result, unlike the conventional struts, the sudden stress changes in the struts are removed. Furthermore, the parameters influencing deep excavation stability are investigated. Basal heave, surface settlement, and lateral deformation of diaphragm walls are determined during geostatic and seismic conditions. Findings of this study provide fundamental principles for designing deep excavations under seismic conditions with efficient strut members. The applicability and effectiveness of the obtained results are also illustrated.